Coronavirus disease 2019: the second wave in Italy - Francesco Chirico; Angelo Sacco; Gabriella Nucera; Nicola Magnavita (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - This paper describes how Italy addressed the first Coronavirus disease 2019 (COVID-19) wave and analyzes the possible causes of the current second wave. Design/methodology/approach - Descriptive analysis of critical points and differences in the containment strategies between the first and the second waves in Italy. Findings - Italy's strict lockdown has been credited with getting the initial major outbreak under control. Furthermore, the way Italy handled the first wave was considered a lesson for other countries. On the contrary, a decentralized and highly bureaucratic political system with low coordination and political conflicts between government, regions and stakeholders led to a relaxation of individual health behaviors, poor and conflicting communication to the general public, poor management of the public transport and the reopening of schools and companies after the summer, that in turn generated the second wave, which is showing signs of becoming worse than the first. Originality/value - This is a commentary piece.